The importance of transformative libraries and librarians role - Ulum, Mochamad Chazienul; Anindyka, Arwin; Sukarno, Karlina Dewi (Jurnal Kajian Informasi dan Perpustakaan, 2025)
Libraries face new challenges amidst social change, digital developments, and increasing disparities in access to information. In this context, there is an urgent need to reposition the role of libraries—not merely as information centers but as agents of empowerment and social transformation. This article aims to examine the significance of implementing the concept of transformative libraries and to formulate the strategic role of librarians in supporting this process. This study employed a qualitative approach using a case study design involving field observations, the CIPP (Context, Input, Process, Product) evaluation model, and a systematic literature review to enrich the analysis. The findings indicated that libraries had great potential to foster local knowledge production, strengthen community literacy movements, and support the democratization of information access. Community participation in managing library services has emerged as a key element in revitalizing libraries as community-based institutions. Challenges such as the digital divide, limited information literacy, and inadequate technological infrastructure emphasized the urgency of redefining the role of libraries. Conversely, librarians were also expected to transform into transformative intellectuals who functioned as facilitators of learning and drivers of social change. This study also developed a model of librarian information behavior that could serve as a reference for professional development in Indonesia. These findings highlight the vital role of transformative libraries as democratic spaces that encourage active community engagement in the lifelong learning process.